Prevalence of Bronchial Asthma and COPD in Comorbidity with COVID-19 - P. G. Svist; N. V. Torchinsky; N. I. Briko; S. N. Avdeev (Эпидемиология и вакцинопрофилактика, 2024)
Relevance. As is known, the presence of some concomitant diseases may be directly related to the severe course of Coronavirus infection and high mortality among the sick. However, the question of the possible impact of bronchial asthma and COPD on outcomes and survival rates in patients with COVID-19 remains relevant. Aim. To evaluate, according to the literature, the prevalence of bronchial asthma and COPD in the general population and among COVID-19 patients in the Russian Federation and in the world, and to determine the degree of their influence on outcomes. Materials and methods. The results of 1080 previously conducted domestic and foreign studies were studied, from which 46 papers were selected that meet the inclusion criteria. Based on the data presented in the studies on the prevalence of bronchial asthma and COPD, the analysis of survival rates, mortality and severity of the consequences of COVID-19 in patients with these pathologies was carried out. Results and discussions. Patients with COPD often had a more severe course of COVID-19, as well as high mortality rates due to the rapid progression of the pulmonary process. Earlier it was reported that patients with bronchial asthma did not notice a negative effect of COVID-19, but the results of recent studies prove the opposite, and therefore further observations are required in this cohort of patients. Conclusion. The presence of COPD has a significant impact on the severity of the course and outcomes of the disease in patients with COVID-19. Timely diagnosis of an infectious disease, qualitative examination, appointment of effective therapy and subsequent rehabilitation with supervision by a specialist have a great importance for patients with COPD. According to the latest data, the presence of bronchial asthma in a number of patients may contribute to a more severe course of COVID-19, but this issue requires further research. At the same time, all patients with chronic lung diseases, without exception, must comply with the basic measures for the prevention of COVID-19 infection and carry out vaccination on time.